Effects of dietary ε-polylysine supplementation on growth performance, antioxidant capacity, immune function, and intestinal microbiota in growing male minks - Wang, Nianxue; Wang, Heliang; Zhang, Xiaowen; Zhao, Lianwen; Li, Wenli; Zhang, Beibei (Frontiers in Microbiology, 2025)
IntroductionThis study investigated the effects of dietary ε-polylysine (ε-PL) supplementation on the growth performance, antioxidant capacity, immune function and intestinal microbiota in growing male minks.MethodsNinety-six 12-week-old male minks were randomly divided into 6 treatments (8 replicates per treatment and 2 minks per replicate). Minks were fed basal diets supplemented with 0 (control), 100, 200, 300, 400, or 500 mg/kg ε-PL for 8 weeks.ResultsCompared with the control, 300–500 mg/kg ε-PL significantly increased the average daily gain (p < 0.05), and significantly decreased the feed-to-gain ratio (p < 0.05) during the whole period and significantly enhanced the body weight at week 8 (p < 0.05), 300–400 mg/kg ε-PL significantly increased the fresh pelt weight (p < 0.05). Compared with the control, 300 mg/kg ε-PL significantly increased serum T-SOD activity and jejunal mucosal T-SOD and GSH-Px activities (p < 0.05). Compared to the control, 200–400 mg/kg ε-PL significantly increased serum IgA level (p < 0.05), 300–400 mg/kg ε-PL significantly increased serum IgM level (p < 0.05), 400–500 mg/kg ε-PL significantly increased serum IgG level (p < 0.05). Compared with the control, 200–400 mg/kg ε-PL significantly increased jejunal mucosal IgA level (p < 0.05), 100 mg/kg ε-PL significantly increased jejunal mucosal IgM level (p < 0.05), 100–400 mg/kg ε-PL significantly increased jejunal mucosal IgG level (p < 0.05). Compared with the control group, all ε-PL supplemented groups significantly decreased serum IL-2 and IL-8 levels compared to the control (p < 0.05). The 16S rRNA sequencing analysis revealed that compared to the control, 300 mg/kg ε-PL significantly increased the relative abundance of Firmicutes and Clostridium_sensu_stricto_1 (p < 0.05), and significantly decreased the relative abundance of Proteobacteria and Escherichia-Shigella in ileal mucosa (p < 0.05). Spearman correlation analysis indicated that the relative abundance of Escherichia-Shigella was negatively correlated with the growth performance. The relative abundance of Clostridium_sensu_stricto_1 was positively correlated with the jejunal mucosal antioxidant indicators and immunoglobulin levels.DiscussionIn conclusion, dietary ε-PL supplementation can improve growth performance, antioxidant capacity, immune function, and gut microbial community in growing male minks, and the optimal dosage of ε-PL is 300 mg/kg.